The THE EFFECT OF TRAINING EFFECTIVENESS, WORKPLACE CULTURE, AND INNOVATION ON THE EFFECTIVENESS OF THE WORK OF SURVEYORS AT SUCOFINDO PT (PERSERO) - SAJIYO, SAJIYO (IJER - INDONESIAN JOURNAL OF EDUCATIONAL REVIEW, 2018)
This study aims to determine the effect of training effectiveness, workplace culture, and innovation on the effectiveness of the work of surveyors. This study uses a quantitative approach using a survey method. Path analysis was used to analyze the data collected. The unit of analysis of this research is the surveyor on Sucofindo PT (Persero) Branch Batam. The number of samples taken in this study, 104 randomly selected people. The results showed that the effectiveness of the surveyor was directly influenced by training effectiveness, workplace culture, and innovation. The study also found that innovation is influenced by training effectiveness and work culture. Based on these findings it can be concluded that any changes are made to the effectiveness of the surveyor is influenced by training effectiveness, workplace culture, and innovation. Therefore, the effectiveness of the surveyor, training effectiveness, workplace culture, and innovation can be taken into consideration in strategic planning for the development of the human resources of a company.